An illustrated history of Indian literature in English - Mehrotra, Arvind Krishna, 1947- (Delhi : Permanent Black in association with Ravi Dayal Publishers, New Delhi ; Bangalore : Distributed by Orient Longman, 2003)
Contributed articles.
"Further reading": p. [381]-389.
Includes index.
Keywords: Indic literature (English) -- 19th century -- History and criticism; Indic literature (English) -- 20th century -- History and criticism